UJI EFEKTIVITAS EKSTRAK DAUN KEMANGI (Ocimum sanctum) SEBAGAI LARVASIDA ALAMI TERHADAP KEMATIAN LARVA NYAMUK AEDES AEGYPTI - Barlian Barlian; Ahmad Ahmad; Rizkia Isfahani (Jurnal Medikes (Media Informasi Kesehatan), 2022)
Ocimum sanctum, known as daun kemangi (Ocimum sanctum)in Indonesia is a plat that is common as fresh vegetables. In addition, Ocimum sanctum also can be used as medicine, vegetable pesticides, making essential oils, vegetables, and refreshing drinks. This study aimed to determine the effectiveness of Ocimum sanctum Extract on the death of Aedes aegypti larvae. This study used the experimental laboratory method. The sample population was Aedes aegypti, with as many as 300 nymphs with a “posttest-only control design.” The concentration of extract Ocimum sanctum used was 1,5%, 2%, 2,5%, dan 3%. Each treatment contained 25 larvae and was observed in 24 hours. The study shows us that an Ocimum sanctum extract concentration of 1,5% was able to kill 36% of larvae, attention of 2% can be able to kill 52%, a concentration of 2,5% was able to kill 68% of larvae, dan concentration of 3% was able to kill 76%. The based engagement was most effective for killing Aedes aegypti larvae at a concentration of 3%.